Tendência da detecção de casos novos de hanseníase com incapaciadade física em Minas Gerais - período: 1995 - 2015 - Karine Chaves Pereira (2016)
Leprosy is a chronic infectious disease that can cause physical disabilities, if not diagnosed and treated early. The disease still persists as a relevant public health problem in several countries, including Brazil. Leprosy is not homogeneously distributed in the country, with higher prevalence rates and detection of new cases in the Midwest, North and Northeast. However, some states in the Southeast also have endemic regions, which is part of Minas Gerais. In 2013 this state presented general leprosy detection rates and in children under 15 years of age above the recommended parameters (6.04/100 thousand inhabitants and 1.10 new cases /100 thousand inhabitants, respectively), a detection rate of new cases with grade 2 disability of 0.59 per 100 thousand inhabitants and a high proportion of new cases with grade 2 disability (9.8%). In this way, it is important to analyze the epidemiological behavior of leprosy in Minas Gerais, focusing on physical disabilities, since the disease is being diagnosed late in the state, which also suggests the existence of diseased persons without diagnosis, which contributes for the continuation of the chain of transmission of the disease and its negative impact on the population. The objective of the study was to analyze the epidemiological trend of leprosy in Minas Gerais from 1995 to 2015, focusing on grade 2 disability. The research refers to an ecological study of time series. The population was composed of the new cases of leprosy registered in the Information System of Notification Diseases resident in Minas Gerais at the date of diagnosis, from 1995 to 2015. For the trend analysis was used the Prais-Winsten regression, with a statistical significance of 5% (p <0.05). The analyzes were performed in the Stata version 12 and Excel version 10 software. The results showed that there was a significant decline of the general leprosy detection rates and of new cases with grade 2 disability in the state, with a decrease of 5.64% and 6.95% per year, respectively. However, the proportion of new cases with grade 2 disability at diagnosis showed a steady trend throughout the period. Despite of the reduction of general leprosy detection rates and of new cases with grade 2 disability, the stable trend of the proportion of new cases with grade 2 disability in the diagnosis predicts late detection and makes it to infer an operational difficulty of the health services to detect leprosy early, contributing to the permanence of the disease transmission chain and its physical, economic and psychosocial consequences.